Formulation and characterisation of micro and macro polypropylene fibre reinforced mortar - Fatiha Bendjilali; Khadra Bendjillali; Krobba Benharzallah (Journal of Building Materials and Structures, 2022)
The objective of this work is to study the physical and mechanical characteristics of mortars reinforced by synthetic fibres. The work is carried out on mortars, using limestone crushing sand, composite cement and synthetic fibres. The fibres used as reinforcement of these mortars are synthetic fibres of polypropylene coming from industrial wastes; micro fibres having a diameter of 0.25 mm and macro fibres with a diameter of 0.45 mm. The used fibres have the same length of 30 mm. The results revealed that the addition of polypropylene fibres has a negative effect on the workability of the mixture, especially micro fibres. However, the mechanical properties of mortars have been enhanced. The weight loss is close in all mortars.